Acid susceptible polymeric stealthy nanoparticles for improved anticancer drug delivery. Issue 18 (11th December 2020) - Shahzadi, Anam; Ikram, Fakhera; Subhani, Riaz Ul Haq; Ahmed, Arsalan; Asif, Anila; Fatima, Nighat; Chaudhry, Aqif Anwar; Hu, Yong
Abstract: Acid stimulus responsive stealthy nanoparticles were prepared by utilizing three types of copolymers, i.e. acid cleavable polycaprolactone-polyethyleneimine-polyethylene glycol (PCL-PEI-PEG), acid charge reversal polycaprolactone-polyethyleneimine (PCL-PEI), and ligand containing polycaprolactone-polyethyleneimine-folate (PCL-PEI-Fol). FTIR, NMR, and UV-visible spectroscopy confirmed the formation of these copolymers. Acid cleavable property of PCL-PEI-PEG copolymer was examined by FTIR. The formation of nanoparticles was determined by DLS and SEM. Aggregation, structural destabilization, and charge reversibility of nanoparticles at low pH were evaluated by DLS, SEM, and Zeta analyzer, respectively. MTT assay was used to evaluate anticancer effect of nanoparticles. Overall, nanoparticles exhibited improved cytotoxic activity against MCF-7 cancer cells. GRAPHICAL ABSTRACT: